PERIKANAN TANGKAP KEMBUNG (RASTRELLIGER SP.) DI PERAIRAN SEKITAR TELUK BUYAT - Ricky Telleng, Aglius Triganus (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The purpose of this research are to explore the indian mackerel fisheries on Buyat Bay by the appearance time and the fishing locations. Daily data of Indian mackerel catching was collected during period August 2004 to May 2009. They were caught by fishermen using handline, drift gillnet and beach seine. The Indian mackerel were caught in Buyat Bay consist of Rastrelliger neglectus and R. kanagurta entered the fishing location in enourmous numbers by three months in every year. The fishing season was occurred in every six months. The fishing location was around Buyat Bay to Racun isle.